Rancangan Desain Pesan Peringatan Dini Bencana Banjir (Studi Komunikasi bencana Pada Badan Penanggulangan Bencana Daerah Kota Bandar Lampung) - Ryu Al-Ikhsan Nur Assyfa; M. Denu Poyo; Noning Verawati (Interaction Communication Studies Journal, 2026)
Flood incidents in Bandar Lampung City have increased significantly, from 11 incidents in 2023 to 242 incidents during January–August 2025, indicating the need for flood early warning communication. This study aims to identify the forms and processes of flood early warning implemented by the Bandar Lampung City Regional Disaster Management Agency (BPBD) and to formulate a warning message design. A qualitative descriptive case study approach was employed. Data were collected through non-participant observation, semi-structured interviews, and documentation involving BPBD officials and residents in flood-prone areas. Data were analyzed through data reduction, data display, and conclusion drawing, with source and technique triangulation used to strengthen data validity. The findings show that BPBD combines conventional and digital forms of flood early warning. Conventional communication, including evacuation signs, socialization, and disaster simulations, supports long-term preparedness, while digital channels such as the Warning Receiver System (WRS), Handy Talky (HT), WhatsApp, and social media support short-term warning dissemination. However, manual field verification and hierarchical communication channels delay information delivery and reduce the time available for community response. Based on these findings, this study proposes an adaptive warning message design integrating the AIDA model and emphasizing simple, timely, accurate, relevant, location-specific, and action-oriented information through Instagram and WhatsApp. The study concludes that effective flood early warning depends not only on communication technology and channels, but also on message design that enables communities to understand risks quickly and take appropriate action.